Mental workload in robotic nephrectomy and nephroureterectomy - 古御堂 純; 加藤 諒; 永森 聖人; 菊地 央; 柏木 明; 熊谷 章 (Japanese Journal of Endourology and Robotics, 2024)
Doctors’ working hours are restricted due to work style reforms. Thus, it is necessary to consider the improvement of working environments aiming at patient safety and the health and safety of medical staff. There have been no reports on the mental workload experienced by urologists during surgery. We compared patient backgrounds and surgical outcomes for cases of laparoscopic and robot-assisted nephrectomy or nephroureterectomy performed in our department. In addition, we collected the background of the four urologists who performed the operations and investigated their mental workload using the NASA-Task Load Index questionnaire.  Laparoscopic surgery was performed in 14 cases (nephrectomy : 11 cases, nephroureterectomy : 3 cases) and robot-assisted surgery in 18 cases (nephrectomy : 5 cases, nephroureterectomy : 13 cases). Robot-assisted surgery was performed more frequently among patients who received nephroureterectomy (p＝0.0035). The operation time was 189 minutes for laparoscopic surgery and 202 minutes for robot-assisted surgery (p＝0.4866), and the amount of blood loss was 55 cc and 45 cc (p＝0.6632), respectively. There was one case of open conversion in laparoscopic surgery because of adhesion due to pyonephrosis, and there was one case of small bowel injury in robot-assisted surgery. We found that the operator’s mental workload was significantly lower in the robotic surgery group than the laparoscopic surgery group (p＝0.0254). Our findings suggest that robot-assisted surgery was as safe as laparoscopic surgery. As robot-assisted surgery is a surgical procedure with less mental workload on doctors, and its use should be expanded in the future.